Seasonal progression and variability of repeat-effort line-drill performance in elite junior basketball players - Montgomery, P. G.; Pyne, D. B.; Hopkins, W. G.; Minahan, C. L. (Journal of Sports Sciences, 2008)
To determine gender differences, positional differences, and patterns of change in the performance of the basketball line-drill test, 93 male (mean age 16.8 years, s = 1.1) and 95 female (mean age 16.5 years, s = 1.0) basketball players undertook 516 line-drill tests over a 5-year period. Log-transformed performance times were analysed using a mixed model that included quadratic within-participant fixed effects for time in the season and time in the programme. Changes and differences were standardized for interpretation of magnitudes. Mean performance times were 28.0 s (s = 1.3) for males and 30.4 s (s = 1.3) for females. The mean pattern of change in performance within a season differed substantially between the sexes and playing positions: male guards and female centres showed moderate to very large improvements mid-season of 1.1% and 3.5% respectively (90% confidence limits ±2.1% and ±3.0%), while female guards and male forwards showed large to very large decrements of -1.6% (±2.6%) and -2.4% (±2.0%). Over 3 years, males improved performance across all three playing positions by 1.4% (±1.3%) and females by 2.9% (±1.4%). Males improved performance by 0.2% (±0.5%) per year, whereas the performance of females deteriorated by 0.6% (±0.4%) per year. The differing patterns of performance change presumably reflect variations in training and competition loads, with short-term fluctuations in performance being managed to promote longer-term improvements.